La implementación de estructuras de hilos de usuario en un sistema operativo didáctico - Ryckeboer, Hugo Emilio (2009)
This is the first attempt of the team to the threads implementation in an operative system with didactic features. In this work we specify the limitations we experienced without going into the analysis of the different threads types. We are also showing here the way the user-level threads structure was plannified with different types of blocked and unblocked sentences, system calls and their problems, the structure of the threads table and the used commands and the reasons why the Kernel–level threads implemenation was not achieved.